The Conceptual Understanding of Sound by Students with Visual Impairments. (March 2013) - Wild, Tiffany A.; Hilson, Margilee P.; Hobson, Sally M.
Introduction: The purpose of the study presented here was to understand and describe the misconceptions of students with visual impairments about sound and instructional techniques that may help them to develop a scientific understanding. Methods: Semistructured interview-centered pre- and posttests were used to identify the students' conceptual understanding. Responses were analyzed using a constant comparative analysis. This process allowed for qualitative data to be collected, analyzed, and coded as an ongoing process to look for gaps, omissions, and inconsistencies in the data and to describe and explore a phenomenon and has been used in prior studies on students' scientific knowledge. Results: The study found that the students had conceptual misconceptions of sound prior to instruction and that their understanding changed on completion of the inquiry-based curriculum. Prior to instruction, none of the students had a complete, scientifically accurate understanding of sound. However, after the study, all the students had some scientific understanding of sound, and two students had a complete scientific understanding of sound. Discussion: The results indicate that using an inquiry-based curriculum is beneficial for students with visual impairments in helping to increase their conceptual understanding. Implications for practitioners: The U.S. Congress has mandated that a curriculum be taught using research-based methodologies and based on standards. The study yielded a methodology to teach sound, a mandated science topic within the standards, that appears to be effective for students with visual impairments.